1998
DOI: 10.1038/sj.onc.1201515
|View full text |Cite
|
Sign up to set email alerts
|

Human growth-differentiation factor 3 (hGDF3): developmental regulation in human teratocarcinoma cell lines and expression in primary testicular germ cell tumours

Abstract: We describe the cloning and initial characterization of a novel cDNA from human embryonal carcinoma (EC) cells. This cDNA, which we named human growth di erentiation factor 3 (hGDF3), encodes the homologue of mouse GDF3, a TGFb superfamily member belonging to the Growth/Di erentiation Factors. We have analysed the expression of hGDF3 in human embryonal carcinoma cell lines and in primary testicular germ cell tumours of adolescents and adults (TGCTs). Expression of hGDF3 in human EC cell lines is stem cell-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 9 publications
1
50
0
Order By: Relevance
“…Thirty-nine of these genes were specifically expressed in embryonal carcinomas compared with seminomas, and among these, GAL was the most significantly differentially expressed gene. Some of the other significant genes have been linked previously to TGCT [i.e., GDF3 (13,14), DNMT3B (15), and BCAT (16)]. Among the 130 genes with higher expression in seminomas, PRAME (preferentially expressed antigen in melanoma) was the most significantly different, and the list also included the previously published SLC43A1 (POV1; refs.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-nine of these genes were specifically expressed in embryonal carcinomas compared with seminomas, and among these, GAL was the most significantly differentially expressed gene. Some of the other significant genes have been linked previously to TGCT [i.e., GDF3 (13,14), DNMT3B (15), and BCAT (16)]. Among the 130 genes with higher expression in seminomas, PRAME (preferentially expressed antigen in melanoma) was the most significantly different, and the list also included the previously published SLC43A1 (POV1; refs.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that GDF3 was also expressed in mature teratoma and in cytotrophoblasts reaffirms that GDF and related gene families may also have an equally important role to play later in organogenesis, as has been suggested by some investigators. 34,35 At the Stem cell markers in testicular germ cell tumors A Gopalan et al same time, the expression of GDF3 in the mature, and not in the immature components of teratoma is somewhat surprising, and needs further investigation. From our results, we believe that strong and diffuse positivity for GDF3 in the right morphological setting and in conjunction with a lack of staining for OCT3/4 and CD30 should aid in the diagnosis of yolk sac tumor.…”
Section: Stem Cell Markers In Testicular Germ Cell Tumorsmentioning
confidence: 99%
“…Although AFP positivity and OCT3/4 negativity is diagnostic of yolk sac tumor, AFP immunohistochemical staining is generally not a very sensitive marker of yolk sac differentiation, showing positive staining in only 55-75% of yolk sac tumors. 18,20 Using RNA protection assays, Caricasole et al 34 found abundant GDF3 expressions in the majority of the non-seminomatous tumors, with the highest expression in embryonal carcinoma and yolk sac tumor and low or absent expression in mature and immature teratoma. Korkola et al 9 also found that the GDF3 gene was significantly overrepresented in embryonal carcinoma, whereas some seminomas showed detectable but very low expression.…”
Section: Stem Cell Markers In Testicular Germ Cell Tumorsmentioning
confidence: 99%
“…Ovary (Dube et al, 1998, Teixeira Filho et al, 2002 Related disorder: Polycystic ovary syndrome (Teixeira Filho et al, 2002) Gdf 3 Embryonal carcinoam cell line (Caricasole et al, 1998) TABLE 2 gene of craniosynostosis. Bmpr1b is important for skeletogenesis.…”
Section: Gdf9mentioning
confidence: 99%